Predonation psychosocial evaluation of living kidney and liver donor candidates: a systematic literature review. (25th July 2013) - Duerinckx, Nathalie; Timmerman, Lotte; Van, Johan; van, Jan; Ismail, Sohal Y.; Massey, Emma K.; Dobbels, Fabienne; ,; Dobbels, Fabienne; Duerinckx, Nathalie; Aujoulat, Isabelle; Poppe, Carine; et al.
Summary Evaluating a person's suitability for living organ donation is crucial, consisting not only of a medical but also of a thorough psychosocial screening. We performed a systematic literature review of guidelines, consensus statements, and protocols on the content and process of psychosocial screening of living kidney and liver donor candidates. We searched PubMed, Embase, CINAHL, and PsycINFO until June 22, 2011, following the PRISMA guidelines, complemented by scrutinizing guidelines databases and references of identified publications. Thirty‐four publications were identified, including seven guidelines, six consensus statements, and 21 protocols or programs. Guidelines and consensus statements were inconsistent and lacked concreteness for both their content and process, possibly explaining the observed variability in center‐specific evaluation protocols and programs. Overall, recommended screening criteria are not evidence‐based and an operational definition of the concept "psychosocial" is missing, causing heterogeneity in terminology. Variation also exists on methods used to psychosocially evaluate potential donors. The scientific basis of predonation psychosocial evaluation needs to be strengthened. There is a need for high‐quality prospective psychosocial outcome studies in living donors, a uniform terminology to label psychosocial screening criteria, and validated instruments to identify risk factors.